SISTEM INFORMASI KEMACETAN LALU LINTAS BERBASIS TEKNOLOGI MOBILE DENGAN TEKNIK GEOFENCING MENGGUNAKAN METODE CROWDSOURCING - Taufiqurrahman -; Apriansyah Putra; Ali Bardadi (Jurnal Informatika, 2017)
Traffic incidents refer to events occurring on highways unrelated to recurring events that interfere with the smoothness and safety of traffic. Congestion is one of the most widespread incidents and has become a problem in big cities. Existing applications do not currently support reporting for favorable conditions of congestion, accidental congestion or other visible incidents on the highways that may help drivers whether to keep picking up stalled routes or alternate routes. In this research, presented a system that supports reporting on the condition or events on the highway that is not only about congestion but also other incidents such as potholes, criminal acts that occur on the highway. The information presented is not the only location but can also be a video or image to show the actual state in visual form. So it can help the user to avoid the congestion area and reduce the buildup of vehicles in the congestion area.Keywords-Information Systems, Traffic Congestion, Geofencing, Crowdsourcing